(untitled) (The International Journal for Scientific Research, 2025)
The principle of continuity (istishab) is one of the rational proofs that a jurist resorts to when specific evidence for a given case is unavailable. The majority of scholars, unlike the Hanafis, consider it one of the agreed-upon proofs after the Quran, Sunnah, and consensus. This research presents a concise overview of the principle of continuity as an introduction to the legal rulings on contemporary issues that fall under its umbrella, since ruling on something is contingent upon understanding it. The research also addresses the rules that fall under the principle of continuity. The research necessitated clarifying some contemporary issues in worship, transactions, and personal status matters, demonstrating the impact of the principle of continuity in determining their rulings and the basis for its application in these cases. The research concludes by establishing criteria for considering the principle of continuity as a legal basis for interpreting new legal issues. These criteria are: - The issue under consideration must be one in which ijtihad (independent reasoning) is permissible. Jurisprudential issues, in their essence, are of two types: those with underlying rationales and those that are divinely ordained and not subject to ijtihad, as the rationale behind their legislation, upon which their rulings depend, is not readily apparent. - A complete jurisprudential understanding of the issue: This is called "jurisprudential classification," which is based on a complete understanding of the case and identifying the principle to which it belongs in order to give it the appropriate legal ruling. - The absence of a text that addresses the case explicitly, implicitly, or through allusion or reasoning. Therefore, a thorough examination of the texts is necessary. If it is established that there is no text on the case, then the principle of continuity (istishab) may be applied, as it is the weakest of the proofs. - The absence of a legal proof that necessitates the cessation of the ruling established in the first instance and contradicts its continuation, such as an abrogating proof. Otherwise, it is obligatory to act upon that proof by consensus. - The absence of something occurring in the second instance that necessitates the cessation of acting upon the ruling established by the first proof.